Distinct Features of Canine Non-conventional CD4−CD8α− Double-Negative TCRαβ+ vs. TCRγδ+ T Cells - Rabiger, Friederike V.; Rothe, Kathrin; von Buttlar, Heiner; Bismarck, Doris; Büttner, Mathias; Moore, Peter F.; Eschke, Maria; Alber, Gottfried (Frontiers in Immunology, 2019)
The role of conventional TCRαβ+CD4+ or TCRαβ+CD8α+ single-positive (sp) T lymphocytes in adap-tive immunity is well recognized. However, non-conventional T cells expressing TCRαβ or TCRγδ but lacking CD4 and CD8α expression (i.e. CD4-CD8α- double-negative (dn) T cells) are thought to play a role at the interface between the innate and adaptive immune system. Dn T cells are frequent in swine, cattle or sheep and predominantly express TCRγδ. In contrast, TCRγδ+ T cells are rare in dogs. In this study, we identified a high proportion of canine dn T cells in the TCRαβ+ T cell population of PBMC, lymphatic and non-lymphatic organs. In PBMC, the frequency of this T cell subpopulation made up one third of the frequency of TCRαβ+CD4+ sp, and almost half of the frequency of TCRαβ+CD8α+ sp T cells (i.e. ~15% of all TCRαβ+ T cells). Among TCRαβ+CD4-CD8α- dn T cells of PBMC and tissues, FoxP3+ cells were identified indicating regulatory potential of this T cell subset. 80% of peripheral blood FoxP3+TCRαβ+CD4-CD8α- dn T cells co-expressed CD25, and, interesting-ly, also the FoxP3-negative TCRαβ+CD4-CD8α- dn T cells comprised ~34% CD25+ cells. Some of the FoxP3-positive TCRαβ+CD4-CD8α- dn T cells co-expressed GATA-3 suggesting stable function of regulatory T cells. The frequency of GATA-3 expression by FoxP3-TCRαβ+CD4-CD8α- dn T cells was even higher as compared with TCRαβ+CD4+ sp T cells (20.6% vs. 11.9%). Albeit lacking FoxP3 and CD25 expression, TCRγδ+CD4-CD8α- dn T cells also expressed substantial proportions of GA-TA-3. In addition, TCRαβ+CD4-CD8α- dn T cells produced IFN-γ and IL-17A upon stimulation. T-bet and granzyme B were only weakly expressed by both dn T cell subsets. In conclusion, this study identifies two dn T cell subsets in the dog: (i) a large (~7.5% in Peyer’s patches, ~15% in lung) popu-lation of TCRαβ+CD4-CD8α- dn T cells with subpopulations thereof showing an activated phenotype, high expression of FoxP3 or GATA-3 as well as production of IFN-γ or IL-17A and (ii) a small TCRγδ+CD4-CD8α- dn T cell subset also expressing GATA-3 without production of IFN-γ or IL-17A. It will be exciting to unravel the function of each subset during immune homeostasis and dis-eases of dogs.